2021
DOI: 10.1113/ep089533
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatation by carbon dioxide and sodium nitroglycerin reduces compliance of the cerebral arteries in humans

Abstract: Changes in vascular resistance and vascular compliance contribute to the regulation of cerebral perfusion. While changes in vascular resistance are known to be mediated by vasodilatation, the mechanisms contributing to changes in vascular compliance are complex. In particular, whether vasodilatation affects compliance of the vasculature within the cranium remains unknown. Therefore, the present study examined the impact of two vasodilatation pathways on cerebrovascular compliance in humans. Fifteen young, heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…These findings open up new facets of the pharmacodynamics of these drugs and expand the understanding of their effects on cerebral hemodynamics. And finally, in a recent clinical study on healthy volunteers 64 , it was shown that dilatation of the middle cerebral artery due to NTG administration was accompanied by a significant decrease in compliance of the downstream cerebral vasculature, which, logically, should lead to a decrease in the amplitude of blood pulsations in intra-parenchymal arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…These findings open up new facets of the pharmacodynamics of these drugs and expand the understanding of their effects on cerebral hemodynamics. And finally, in a recent clinical study on healthy volunteers 64 , it was shown that dilatation of the middle cerebral artery due to NTG administration was accompanied by a significant decrease in compliance of the downstream cerebral vasculature, which, logically, should lead to a decrease in the amplitude of blood pulsations in intra-parenchymal arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…Other associated parameters are sedation depth-related parameter BIS (Froese et al 2021), respiratory oscillations-related parameter GainFV (Haubrich et al 2015, Varsos et al 2015, thiopental treatment (Howells et al 2012), cerebral hemodynamic instability (Pineda et al 2018), pressure reactivity (Shahsavari et al 2011, Kim et al 2012, transfer function between ABP and ICP (Budohoski et al 2012), hyperventilation (Steiner et al 2005, Carrera et al 2011, CT-image (Zeiler et al 2018b), ICP spindle waves (Zhu et al 2023), phase shift angle between CBFV and ICP (Kim et al 2015), the resistance to CSF outflow (Kim et al 2009a), VMR (Haubrich et al 2013), hypocapnia-hypercapnia (Carrera et al 2011a, Haubrich et al 2013, supratentorial and infratentorial compartment (Moyse et al 2016), age (Kiening et al 2005), ultrasoundguided aspiration (Ng et al 2005), arterial hypertension (Kim et al 2012), plateau waves (Kim et al 2009b), CVR (Capel et al 2014), L/P ratio (Salci et al 2006), brain elasticity (Kim et al 2010), internal carotid artery disease (Carrera et al 2011b), and SNG and hypercapnia protocol (Moir et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another study was conducted on healthy subjects, experimenting with the effect of sublingual sodium nitroglycerin (SNG) protocol and hypercapnia protocol. In both cases, cerebrovascular compliance decreased, with hypercapnia protocol associated with a comparatively higher reduction (Moir et al 2021).…”
Section: Studies With Other Patient Patientsmentioning
confidence: 91%
See 1 more Smart Citation
“…Much like the rest of the body, the CNS vasculature responds to compounds such as nitroglycerin [14][15][16] and sodium nitroprusside, [17,18] which cause rapid vessel dilation. However, direct investigation of the effects of local blood flow modulation on the CNS tissues is difficult.…”
Section: Introductionmentioning
confidence: 99%